Steal my breath away - Castille, Sarah (Castille, Sarah. Havencrest U, 2025)
"Emotions run high, but the tempo thrums higher as music, heat, and angst collide between a singer and her bodyguard. Haley Chapman has struggled against rules all her life. As the daughter of a senator, she's expected to finish her college degree, but music is her one true love -- the only outlet she has for her wild, impulsive feelings. When Haley becomes the target of a brazen kidnapping attempt linked to her mother's high-profile Senate career, the Senator insists on round-the-clock protection. Having a security detail follow her around college feels like overkill, but the Senator has the perfect solution. Ace Murphy was her brother's best friend, and a former Air Force pilot, now working in personal security as a celebrity bodyguard. He was also Haley's teenage crush and the man who abandoned her when she needed him most, breaking her fragile heart. Now, as Ace poses as her boyfriend on campus, their personalities clash. He may be her protector but to Haley, Ace is just another obstacle to her freedom and a painful reminder of the past. But as the threats escalate, their forced proximity ignites a connection they can't ignore -- one that could either save them or break them all over again"-- Provided by publisher.